Ampliação da colegialidade: técnica de julgamento do artigo 942 do Código de Processo Civil - Rivaroli, Bruna Valentini Barbiero (2018)
The present dissertation is to analyze, through a vast bibliographic research, the technique of expanding the judicial panel inserted in article 942 of the New Civil Procedure Code. As regards structure, the work is divided into five chapters. The first chapter deals with the historical evolution of appeals on the grounds of request for reconsideration (embargos infringentes) in Portuguese legislation, from the creation of appeals on the grounds of request for reconsideration (embargos infringentes) until the evolution that were extinguished in 1939, also analyzes the Brazilian legislation until their extinction. The second chapter presents the constitutional model of New Civil Procedure Code and the guiding principles that justified the extinction of the appeals on the grounds of request for reconsideration (embargos infringentes). In addition, the entire CPC process was analyzed, from the preliminary project until its approval in order to show reasons for the creation of the technique to replace. The third chapter, in turn, deals specifically with the technique, its particularities and hypotheses of application and non-application provided by law, not to mention the analysis of the internal regulations of different Courts of Justice. The four chapter addresses the operational problems of application of the technique related to which resources is intended, issues of expiry legislation and, also, respect to the contradictory. Finally, the fifth chapter is devoted to the analysis of judgments of the Court of Justice of São Paulo and also of other Courts in order to try to understand the application of the technique after a year of validity of the CPC of 2015